2021
DOI: 10.1093/cid/ciaa1910
|View full text |Cite
|
Sign up to set email alerts
|

Fujifilm SILVAMP TB LAM Assay on Cerebrospinal Fluid for the Detection of Tuberculous Meningitis in Adults With Human Immunodeficiency Virus

Abstract: Background Tuberculous meningitis (TBM) has a high fatality rate with inadequate diagnostic tests being a major contributor. The rollout of Xpert MTB/Rif and Xpert MTB/Rif Ultra (Xpert Ultra) have improved time-to-diagnosis with sensitivities similar to culture, yet test availability and sensitivity are inadequate. The TB lipoarabinomannan lateral flow assay (AlereLAM) offers ease of use, but its low sensitivity in cerebrospinal fluid (CSF) limits clinical utility for TBM. The Fujifilm SILVAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…After full-text screening of the remaining studies, five were excluded because they were reviews, two were excluded because they did not evaluate the diagnostic value of FujiLAM, and one article was excluded because there were potentially repeat data (Figure 1). Finally, a total of nine articles that described the value of FujiLAM in the diagnosis of TB patients were identified (11)(12)(13)(14)(17)(18)(19)(20)(21)). Among them, three studies reported the diagnostic value of FujiLAM in pediatric patients with TB, while the rest were the diagnostic value of FujiLAM in adult patients with TB.…”
Section: General Characteristicsmentioning
confidence: 99%
“…After full-text screening of the remaining studies, five were excluded because they were reviews, two were excluded because they did not evaluate the diagnostic value of FujiLAM, and one article was excluded because there were potentially repeat data (Figure 1). Finally, a total of nine articles that described the value of FujiLAM in the diagnosis of TB patients were identified (11)(12)(13)(14)(17)(18)(19)(20)(21)). Among them, three studies reported the diagnostic value of FujiLAM in pediatric patients with TB, while the rest were the diagnostic value of FujiLAM in adult patients with TB.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Tuberculous meningitis (TBM), the central nervous system tuberculosis caused by MTB infection, is the most severe complication of TB ( 29 ). TBM has a high fatality rate, mainly due to insufficient diagnostic testing ( 30 ). Although the World Health Organization recommends the GeneXpert MTB/RIF assay technology, its sensitivity is still <60% ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, considering some challenges faced during the testing procedure such as result readability, with one healthcare worker failing to correctly interpret the results during the proficiency evaluation, it may be necessary to offer more training and supervision for all healthcare workers regardless of medical training background during implementation to ensure correct result interpretation. Difficulties to read faint result lines were also experienced in a study using FujiLAM to test cerebrospinal fluid [30] . The proficiency evaluation tool we used, developed by FIND, would be very useful to identify individuals requiring more support as well as the specific support required.…”
Section: Discussionmentioning
confidence: 99%